2023
DOI: 10.1029/2023ja031526
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Assessment of the Distribution of Joule Heating in Altitude as Estimated in TIE‐GCM and EISCAT Over One Solar Cycle

D. Baloukidis,
T. Sarris,
S. Tourgaidis
et al.

Abstract: During geomagnetically active times, Joule (or frictional) heating in the Lower Thermosphere‐Ionosphere is a significant source of thermal energy, greatly affecting density, temperature, composition and circulation. At the same time, Joule heating and the associated Pedersen conductivity are amongst the least known parameters in the upper atmosphere in terms of their quantification and spatial distribution, and their parameterization by geomagnetic parameters shows large discrepancies between estimation method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 75 publications
2
4
1
Order By: Relevance
“…The factor f = 1.5 has been implemented in the TIE-GCM as the default factor and, as shown in this study, seems to be appropriate as average factor for all convection models, magnetic local times and geophysical conditions. The general trend that the largest q J occurs around midnight and the lowest q J is observed around noon magnetic local time agrees well with previous studies (e.g., Baloukidis et al, 2023;Rodger et al, 2001). The exception is that when applying EISCAT plasma parameters at Kp > 4, the strongest Joule heating is found in the dusk MagLT sector.…”
Section: Earth and Space Sciencesupporting
confidence: 91%
See 4 more Smart Citations
“…The factor f = 1.5 has been implemented in the TIE-GCM as the default factor and, as shown in this study, seems to be appropriate as average factor for all convection models, magnetic local times and geophysical conditions. The general trend that the largest q J occurs around midnight and the lowest q J is observed around noon magnetic local time agrees well with previous studies (e.g., Baloukidis et al, 2023;Rodger et al, 2001). The exception is that when applying EISCAT plasma parameters at Kp > 4, the strongest Joule heating is found in the dusk MagLT sector.…”
Section: Earth and Space Sciencesupporting
confidence: 91%
“…However, since our data includes comparably few measurements during summer, the dusk maximum of Joule heating found in this paper might not be related to the findings by Foster et al (1983). Baloukidis et al (2023) showed that this trend is also found in TIE-GCM runs driven by the Weimer convection model. However, the variation of Joule heating with magnetic local time is not exactly reproduced by the model which introduces increased heating rates for MagLT noon time and lower heating rates during the rest of the day (Baloukidis et al, 2023).…”
Section: Earth and Space Sciencecontrasting
confidence: 67%
See 3 more Smart Citations